Endogenous skill biased technical change: Testing for demand pull effect - Francesco Bogliacino; Matteo Lucchese (Luxembourg Income Study (LIS), 2011)
In this article we use the unification of Germany in the 1990 to test the hypothesis that the increase of the supply of a production factor generates skill biased technical change. We test for this mechanism in the context of the Acemoglu and Autor (2011) model that allows for endogenous assignment of skills to tasks in the economy. We use cohorts of workers from comparable countries as a control groups. After discussing the possible confounding factors, we conclude for the absence of this effect. The differential pattern among the countries seems to be determined by labor market flexibilization and tax reform, which had a pure inequality enhancing effect.
Keywords: J31; O33; O52; 330; Polarization; Skilled Biased Technological Change; Demand Pull